Sources for the history of science: the hygiene of clothes in Puebla - Huerta Jaramillo, Ana Maria Dolores (Circumscribere International Journal for the History of Science, 2012)
In the 19th century, a wide variety of printed texts were published in Mexico aiming at influence the housekeeping behavior of women. Appearing as handbooks, letters, notes, daybooks, and books, several national and foreign authors translated medical and chemical authors into the everyday language. A short discussion of documents allows witnessing how the development of science attributed specific roles to women, in particular the ones related with hygiene.